A rare case of pediatric medulloblastoma presented with radiographic characteristics of pontine glioma - ., Kartika; Ayusta, I. Made Dwijaputra; Asih, Made Widhi (International Journal of Research in Medical Sciences, 2019)
Medulloblastoma is a common malignant brain tumor of childhood which characterized as an infratentorial mass in the roof of the 4th ventricle, causing mass effect and non-communicating hydrocephalus. A 3 years old boy with history of chronic progressive weakness one-month prior admission, followed by difficulty in walking and ataxia. His MRI examination showed an intraaxial well defined mass, partial irregular border, size 4.2x4.0x4.1 cm at pons, hypointense in T1W1, hyperintense in T2W1, iso-hypointense in flair, and showing inhomogen contras enhancement after gadolinium administration. It pressed the 4th ventricle without dilatation of other ventricles, suggesting a pontine glioma. Patient underwent surgery to remove mass and the pathological examination revealed small round cells, with differential diagnose of medulloblastoma and anaplastic astrocytoma. This case presented as there was a discrepancy in the clinicoradiological diagnosis with the pathological diagnose of medulloblastoma. The mass was located at the pontine without any sign of hydrocephalus suggested a pontine glioma. Both medulloblastoma and pontine glioma are common for infratentorial mass of pediatric population, but difficult to diagnose due to its heterogeneous presentation. Good comprehension of both radiological characteristics is noteworthy.